Transition from milks to the introduction of solid foods across the first 2 years of life: findings from an Australian birth cohort study. Issue 4 (20th April 2015) - Amezdroz, E.; Carpenter, L.; O'Callaghan, E.; Johnson, S.; Waters, E.
Abstract Background The current literature regarding the transition from milks to solid foods across the first 2 years of life is limited despite the important influence of early dietary intake on children's growth and development. The present study describes dietary intake from birth to 2 years across four developmental relevant time‐points within an Australian birth cohort. Methods Dietary data from 466 infants was collected at four time‐points in the first 2 years of life via parent‐reported questionnaire, including a 45‐item food and beverage frequency questionnaire. Subsample analyses of children who were aged 1–3, 6–8, 12–14 and 18–20 months at the time of data collection were conducted. Results Infant formula remained consistently consumed by over 75% of children from the 6–8‐ to 18–20 months old age groups. Mean (SD) age of introduction to solid foods was 5.2 (1.3) months. Almost 20% and 10% of children were introduced before 16 and after 32 weeks, respectively. The highest consumption of core foods, recommended for a healthy diet, daily was seen in the 12–14 months old age group with lower proportions in the 18–20 months old age group coinciding with an increased proportion of children eating discretionary choice foods, not recommended for a healthy diet. Discretionary choice foods/beverages presented in children's diets as early as in the 6–8 months old age group. By 18–20 months, at least 20% of children were consuming savoury biscuits, sweet biscuits, muesli bars and luncheon meats at least twice a week. Conclusions The present study identified a number of findings outside the recommendations of the Australian Dietary and Infant Feeding Guidelines. Further work is warranted to explore these outcomes.